Trade and Growth in the Presence of Distortions - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 2005)
Tariffs and other policy distortions typically lower real national income relative to what it otherwise would have been for any given rate of factor accumulation. Even while lowering real income, however, policy distortions may raise an economy's real measured growth rate and so, somewhat deceivingly, give the impression that national welfare has benefited from things like tariff protection. This would be an incorrect conclusion. This paper discusses the issue of how protection can affect the rate of growth for a small, open economy. As shown by Johnson (1970), in the presence of exogenously given factor accumulation, tariffs either raise or lower an economy's growth rate (measured by the change in the value of output at world prices), relative to the no-distortion growth rate. We also discuss the relevance of this result for tariff uniformity, "tariff jumping" foreign direct investment, and the empirical literature on trade and growth. Finally we use a numerical simulation model of Egypt to assess whether the costs of its tax distortions have increased or declined over time.